«Io vivo fra le cose e invento, come posso, il modo di nominarle» Pier Paolo Pasolini e la lingua della modernità - Venturi, Maria Teresa (Premio Tesi di Dottorato, 2020)
This study's aim is to deepen and enhance the linguistic dimension in Pier Paolo Pasolini's work, in the hope of restoring to his figure all the fullness of his intense and visceral relationship with the entire universe of languages. In the first part of the work we will investigate the various moments of Pasolini's reflection on different expressive codes, from dialect to the language of cinema, from the 'Language of Reality' to the technological neo-Italian, promptly counterposed by the author's linguistic experimentation. From here a broad lexical investigation starts - this study being the subject of the second part of this volume - with the aim of highlighting the author's contribution to contemporary Italian (as to this day many 'keywords' from Pasolini's universe still echo in Italian language, from «nuovo Potere» to «Palazzo», from «omologazione» to «mutazione antropologica»), thus confirming, once again, the inseparable relationship between reflection and language creativity, giving birth to a new, unique portrait of Pasolini as a 'linguist' and at the same time as an 'onomaturgist'.